Charged and neutral particles beams application for research of accumulation routes of the medical radioisotope ¹⁰³Pd - Hryhorenko, V.O. (Problems of Atomic Science and Technology, 2023)
The results of experimental data analysis about the accumulation routes of the important medical isotope ¹⁰³Pd induced by charged particle beams (protons, deuterons, helium-3, helium-4) and neutral particles (gamma and neutrons) are presented. The main generalized data about the nuclear reaction cross-section of ¹⁰³Pd production versus the irradiation techniques of natural and isotope-enriched targets and their content of unwanted accompanying radio nuclides were compared to theoretical predictions of too. The optimization procedure of the ¹⁰³Pd accumulation is discussed in order to develop more promising ones, taking into account the requirements for the production of medical radioisotopes.